Marginalization of “the Other”: Gender Discrimination in Dystopian Visions by Feminist Science Fiction Authors - Gilarek, Anna (Text Matters: A Journal of Literature, Theory and Culture, 2012)
In patriarchy women are frequently perceived as “the other” and as such they are subject to discrimination and marginalization. The androcentric character of patriarchy inherently confines women to the fringes of society. Undeniably, this was the case in Western culture throughout most of the twentieth century, before the social transformation triggered by the feminist movement enabled women to access spheres previously unavailable to them. Feminist science fiction of the 1970s, like feminism, attempted to challenge the patriarchal status quo in which gender-based discrimination against women was the norm. Thus, authors expressed, in a fictionalized form, the same issues that constituted the primary concerns of feminism in its second wave. As feminist science fiction is an imaginative genre, the critique of the abuses of the twentieth-century patriarchy is usually developed in defamiliarized, unreal settings. Consequently, current problems are recontextualized, a technique which is meant to give the reader a new perspective on certain aspects of life they might otherwise take for granted, such as the inadequacies of patriarchy and women’s marginality in society. Yet there are authors who consider the real world dystopian enough to be used as a setting for their novels. This is the case with Woman on the Edge of Time by Marge Piercy and The Female Man by Joanna Russ. Both texts split the narrative into a science fictional and a realistic strand so as to contrast the contemporary world with utopian and dystopian alternatives. Both texts are largely politicized as they expose and challenge the marginalized status of women in the American society of the 1970s. They explore the process of constructing marginalized identities, as well as the forms that marginalization takes in the society. Most importantly, they indicate the necessity of decisive steps being taken to improve the situation.